O papel dos rins no equilíbrio ácido-básico em cães submetidos aos efeitos do halotano e hipercapnia - Yong, L. C.; Vianna, Pedro Thadeu Galvão [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Vane, Luiz Antonio [UNESP] (My University, 1979)
In eighteen dogs, the effects of halothane (0,75% and 1,5%) associated with a normo and hypercapnia (PaCO2 from 30 to 80 mmHg) on acid-base balance were studied. Determinations of creatine clearance, urinary flow, urinary acid excretion, and urinary ammonium excretion were made. Based on the results, it is concluded that halothane associated with hypercapnia decreases the glomerular filtration rate, the urinary flow, the urinary pH and the urinary bicarbonate and sodium excretion, increases the plasmatic bicarbonate concentration, the bicarbonate reabsorbed, the urinary acid excretion and the urinary ammonium excretion, but does not alter the base excess.
Role of the kidney in acid-base balance in dogs, submitted to effects of halothane and hypercapnia
Keywords: carbon dioxide; halothane; acid base balance; animal experiment; blood and hemopoietic system; central nervous system; dose response; drug response; hypercapnia; inhalational drug administration; kidney function